Recent Advances in Conversion of Glycerol: A Byproduct of Biodiesel Production to Glycerol Carbonate - Arpita Das; Pravin Kodgire; Hu Li; Sanjay Basumatary; Gurunathan Baskar; Samuel Lalthazuala Rokhum (Journal of Chemistry)
Owing to erupted ecological concerns and escalated energy consumption, biodiesel produced by transesterifying nonedible and used cooking oils has been acknowledged as a viable source of clean and sustainable energy, alternative to fossil fuels. This transesterification process led to an excessive supply of glycerol as the primary byproduct which can then be transformed into value-added derivatives, primarily glycerol carbonate (GC), thereby drawing attention to its potential use in industrial applications. Although several methods for synthesis of GC utilize glycerol as building block, the transesterification approach using dimethyl carbonate (DMC) is the most effective route implementing safer and greener reaction conditions. This review is focused on different types of heterogeneous catalysts and characterization techniques used for identifying and deactivating those catalysts, covering the literature from the last decade to till date on this topic. Potent applications of GC as a versatile compound are elucidated in brief. Finally, a conclusion, outlook, and author’s perspective have been provided in brief.